Spatial Characterization of the Human Centrosome Proteome Opens Up New Horizons for a Small but Versatile Organelle. Issue 23 (26th August 2020) - Danielsson, Frida; Mahdessian, Diana; Axelsson, Ulrika; Sullivan, Devin; Uhlén, Mathias; Andersen, Jens S.; Thul, Peter J.; Lundberg, Emma
Abstract: After a century of research, the human centrosome continues to fascinate. Based on immunofluorescence and confocal microscopy, an extensive inventory of the protein components of the human centrosome, and the centriolar satellites, with the important contribution of over 300 novel proteins localizing to these compartments is presented. A network of candidate centrosome proteins involved in ubiquitination, including six interaction partners of the Kelch‐like protein 21, and an additional network of protein phosphatases, together supporting the suggested role of the centrosome as an interactive hub for cell signaling, is identified. Analysis of multi‐localization across cellular organelles analyzed within the Human Protein Atlas (HPA) project shows how multi‐localizing proteins are particularly overrepresented in centriolar satellites, supporting the dynamic nature and wide range of functions for this compartment. In summary, the spatial dissection of the human centrosome and centriolar satellites described here provides a comprehensive knowledgebase for further exploration of their proteomes.